2013
DOI: 10.1097/dbp.0b013e3182a5095f
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation is Related to Children's Emotional and External Eating

Abstract: Given the established link in previous research between poor behavioral regulation and obesity in children, findings from this study linking child emotional reactivity and emotional and external eating (both forms of behavior dysregulation) are important in informing prevention and treatment programs. Based on these findings, targeting child emotion regulation in addition to behavior regulation skills as part of prevention and intervention programs may improve program effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 45 publications
4
59
0
Order By: Relevance
“…As a result of these symptoms, girls and youth with self-reported LOC may be more inclined to social isolation and inactivity when a stressor arises, thereby contributing to an energy imbalance promoting body mass gains. Boys, in contrast, tend to engage in externalizing behaviors when stressed (Harrist et al, 2013). Alternatively, the methods used in the current study may not have captured energy intake associated with emotion dysregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of these symptoms, girls and youth with self-reported LOC may be more inclined to social isolation and inactivity when a stressor arises, thereby contributing to an energy imbalance promoting body mass gains. Boys, in contrast, tend to engage in externalizing behaviors when stressed (Harrist et al, 2013). Alternatively, the methods used in the current study may not have captured energy intake associated with emotion dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Emotion dysregulation is also positively associated with junk food intake among adolescent girls (Isasi, Ostrovsky, & Wills, 2013) and general disordered eating patterns, including self-reported LOC eating, among high school students (Mills, Newman, Cossar, & Murray, 2015). Emotion dysregulation also predicts 1-year increases in emotional and external eating among children (Harrist, Hubbs-Tait, Topham, Shriver, & Page, 2013). Data from these studies suggest that emotion dysregulation is associated with a range of self-reported eating behaviors characterized by excess energy intake, including self-reported LOC eating.…”
mentioning
confidence: 99%
“…17 Disturbed eating behaviors, such as emotional and external eating patterns, are potential mediators of this association. 30 in addition, low self-esteem and feelings of guilt and personal failure characterize both obesity and internalizing problems. 31,32 Furthermore, the obesogenic effect of reduced sleep is thought to be mediated by both behavioral and hormonal factors.…”
Section: Discussionmentioning
confidence: 99%
“…The affect regulation model (3940), which is used with adults, suggests a link between the inability to deal with negative emotions and unhealthy coping (e.g., turning to food), but it has not been used with children. We tested our hypothesis in a longitudinal study of second and third graders (41). Children’s emotion regulation (reactivity to and inhibition of anger and worry) correlated significantly with their external and emotional eating regulation within and across grades.…”
Section: The Families and Schools For Health Projectmentioning
confidence: 99%